National Evaluation of the Violent Offender Incarceration/Truth-in-Sentencing Incentive Grant Program, 1996-1999 - Turner, Susan ([Verlag nicht ermittelbar], 2003)
This study evaluated the Violent Offender Incarceration/Truth-in-Sentencing (VOI/TIS) incentive grant program enacted in 1994. The program provided grants to states to be used to increase the capacity of state correctional systems to confine serious and violent offenders. This national evaluation addressed four broad areas: (1) How had the federal government implemented the law? How much money had been made available and what were the criteria for disbursement? (2) How had the states reacted legislatively to the law? Did states adopt truth-in-sentencing or statutes having equivalent effect? (3) How had the state VOI/TIS money been spent and for what? How much did it increased prison capacities? (4) Did the law increase the number of admissions, length of sentences, and terms served for violent offenders? In addition to these four major areas, the study looked at related areas of interest, such as the impact of VOI/TIS and other "get tough" legislation on prosecutorial and judicial attitudes, policies, and practices. It also examined state spending on corrections, particularly for construction. The researchers collaborated with the American Correctional Association (ACA), the American Prosecutors Research Institute (APRI), and the Justice Management Institute (JMI) to conduct special surveys among state correctional officials, prosecutors, and judges. The ACA surveyed state departments of correction in the summer of 1998. States were asked to indicate the extent of changes in a number of prison operations and activities since 1996, when VOI/TIS funds became available. In the summer of 1999 the APRI surveyed prosecutors nationwide to ascertain their perceptions of the effects of "get tough" legislation (including TIS) on a number of dimensions. In the fall of 1999, the JMI surveyed judges nationwide on their impressions of the effectiveness of several "get tough" measures in their states, including VOI/TIS. In Part 1, American Correctional Association Survey Data, state correction departments were questioned on the amount of VOI/TIS funds spent by their state since 1996, number of beds added using VOI/TIS funds and in what types of facilities, how VOI/TIS funds were used to increase number of beds, average prison sentences in 1993 and 1998 for different types of offenses, average time actually served in 1993 and 1998 for those offenses, the effects of VOI/TIS on prison and jail admissions for different types of offenders, and its effects on the composition of the prison population, prison inmate activities and programs, prison staffing, and prison operations. In Part 2, American Prosecutors Research Institute Survey Data, prosecutors were questioned about what "get tough" policies their states had enacted, the efficacy of "get tough" policies in achieving their goals, whether these policies had unanticipated or negative consequences, expected results of these policies, the percentage of cases to which these policies applied, the extent to which these policies had helped accomplish their office's goals, the effects of "get tough" policies on budget and resources, sentences and time actually served, and the criminal justice process, the size of their jurisdiction, and the number of staff in their office. In Part 3, Justice Management Institute Survey Data, judges were questioned about whether their state had enacted "get tough" policies in the past ten years, what kinds of policies were adopted, their effect on the efficiency of case processing, the formal positions of the Judicial Council and Judges Association on the policies, whether the respondent or other judges had input into the policies, how likely "get tough" policies were to achieve certain goals, what results the respondent expected from the policies, the impact of the policies on the criminal justice process, years experience on the bench, the percentage of their caseload that involved criminal cases, whether they handled civil, family law/domestic relations, or juvenile cases, and the population of their jurisdiction.